Foresight Studies of Global Food Security: Model-Based, Long-Run Scenario Analysis - Robinson, Sherman (2013)
"Partnering for Impact: IFPRI-European Research Collaboration for Improved Food and Nutrition Security" presentation by Sherman Robinson, IFPRI, on 25 November 2013 in Brussels, Belgium.